Algorithms for the restriction-site mapping of DNA molecules. - Krawczak, M (1988)
Two algorithms are described that rapidly construct restriction maps of DNA molecules from single- and double-digest data. The implementation of these algorithms into the Pascal programs AMAPK and AMARD allows such mapping to be done on microcomputers.